Aplikasi Terjemah Bahasa Madura Ke Bahasa Indonesia, Bahasa Indonesia Ke Bahasa Madura Berbasis Android - Wijaya, Anud; Misdiyanto, Misdiyanto; Aprilia, Ira (INTRO : Journal Informatika dan Teknik Elektro, 2022)
Probolinggo is a city or district in the province of East Java which is located in the east of the province of East Java which is adjacent to the island of Bali. The city district of Banyuwangi has a unique language that is different from other Javanese languages. In the knowledge of the meaning of words from the probolinggo language which is very minimal, a Madura language dictionary in the form of a book is held, it is feared that it will be damaged or otherwise, an auxiliary application is held in which the application will preserve the cultural language of the city of Probolinggo. In this study using the waterfall method model, in this method there are several stages including research and development procedures, needs analysis, system design, program code writing, program testing. Distribution in making applications for translation from Madura to Indonesia, Indonesian to Madurese using Android Studio. After all the steps above are done, then an application is created to translate Madura to Indonesian, Indonesian to Madurese according to needs. This translation application produces output that includes the people of the city of Probolinggo. Keywords - Translation Application, Madurese-Indonesian Language, Android Studio, Probolinggo.